Next stop Ga-aynd-ah! : 100 years of Gayndah railway stories - Slack, Jill. (Gayndah, Qld. : J. Slack, 2007)
"An anecdotal history of how the railway impacted on Gayndah's social dimensions, industries and development throughout the last century."--Provided by publisher.
Includes bibliographical references.
Keywords: Railroads -- Queensland -- Gayndah -- History; Gayndah (Qld.) -- History